Manfaat Pemeriksaan Kinerja terhadap Auditee Badan Pemeriksa Keuangan Republik Indonesia - Nico Andrianto; Andi Wibowo; Budiman Sihaloho (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
Benefit of implementating audit recommendation is an important factor in performance audit. This paper present results of descriptive research using survey method to auditee of BPK’s performance audit aimed to assess the extent of benefits of BPK’s performance audit and to know BPK’s performance audit recommendation over entities being audited (auditee). Survey was conducted to BPK’s auditees that consist of Ministries/agencies, state/local owned enterprises, hospitals, as well as regional work units (SKPD) in Provincial/District/City government and “other entities”. The survey results show that BPK’s performance audit help improving the performance of the auditee, where auditee at regional government level (including local owned enterprises) get greater benefit than the central government (including state owned enterprises). The survey result shows higher frequency of performance audit conducted and better quality of BPK’s recommendation provides greater benefits to the auditee. This survey also shows that 90% of respondents agree that BPK’s recommendations can be implemented. Some inputs presented by the auditee related efforts should to be taken by the BPK to improve the quality of audit and recommendation, to increase the level of follow up by the auditee.